Apical and basolateral endocytosis in Madin-Darby canine kidney (MDCK) cells grown on nitrocellulose filters. - von Bonsdorff, C H (1985)
Madin-Darby canine kidney (MDCK) cells (strain I) grown on 0.45 micron pore size nitrocellulose filters formed monolayers which were highly polarized and had high transepithelial electrical resistance (greater than 3000 ohm X cm2). Morphometric analysis showed that the area of the basolateral surface domain was 7.6 times larger than that of the apical. The uptake of fluid-phase markers [3H]inulin and horseradish peroxidase (HRP) was studied from the apical and the basal side of the monolayer. Uptake of [3H]inulin was biphasic and the rate during the first 40 min corresponded to a fluid phase uptake of 20.5 X 10(-8) nl/min per cell from the basolateral side, and 1.0 X 10(-8) nl/min per cell from the apical side. Electron micrographs of the monolayers after HRP uptake showed that the marker was rapidly delivered into endosome-like vesicles and into multivesicular bodies. No labelling of the Golgi complex could be observed during 2 h of uptake. Evidence was obtained for the transport of fluid phase markers across the cell. HRP and fluorescein isothiocyanate-dextran crossed the monolayers in either direction at a rate corresponding to approximately 3 X 10(-8) nl of fluid/min/cell. Adding the transcytosis rate to the rate of fluid accumulation into the cell yielded a total basolateral endocytic rate which was 6-fold greater than the apical rate. When the uptake rates were normalized for membrane area the apical and basolateral endocytic rates were about equal per unit cell surface area.